Molecular structure, bioavailability and bioactivity of [Cu(o-phen)2(cnge)](NO3)2 · 2H2O and [Cu(o-phen)(cnge)(H2O)(NO3)2] complexes - Ferrer, Evelina Gloria (2007)
Two Cu(II) complexes with cyanoguanidine (cnge) and o-phenanthroline, [Cu(o-phen)2(cnge)](NO3)2 · 2H2O (1) and [Cu(o-phen)(cnge)(H2O)(NO3)2] (2), have been synthesized using different experimental techniques and characterized by elemental analyses, FTIR, diffuse and UV-vis spectra and EPR and magnetic moment measurements techniques. The crystal structures of both complexes were solved by X-ray diffraction methods. Complex (1) crystallizes in the monoclinic space group C2/c with a = 12.621(5), b = 31.968(3), c = 15.39(1) Å, β = 111.68(4)°, and Z = 8 and complex (2) in the monoclinic space group P21/n with a = 10.245(1), b = 13.923(2), c = 12.391(2) Å, β = 98.07(1)°, and Z = 4. The environments of the copper(II) center are trigonal bipyramidal (TBP) for [Cu(o-phen)2(cnge)]2+ and an elongated octahedron for [Cu(o-phen)(cnge)(H2O)(NO3)2]. Solution studies have been performed to determine the species distribution. The superoxide dismutase (SOD) activities of both complexes have also been tested in order to determine if these compounds mimic the enzymatic action of the enzyme SOD that protects cells against peroxide radicals. © 2007 Elsevier Inc. All rights reserved.